A Single Theoretical Descriptor for the Bond-Dissociation Energy of Substituted Phenols - Caroli-Rezende, M; Aliaga-Vidal, C; Aliaga-Vidal, C; Almodovar-Fajardo, I (Springer Verlag, 2015)
Relative to the corresponding value of phenol, the bond-dissociation energies (BDE) of substituted phenols correlate well with a single descriptor: the Mulliken charge on the oxygen atom of the phenoxyl radical. However, the correlation fails for phenols ortho-substituted with polar groups. Internal reaction coordinates (IRC) for the model reaction of hydrogen abstraction by the hydroperoxyl radical from various 2- and 4-substituted phenols were calculated in order to investigate the role of intra-molecular hydrogen bonds and steric effects on the process. Calculations yielded theoretical values in good agreement with experimental ΔBDE values. The hydrogen-abstraction process was further analyzed in terms of density functional theory (DFT)-based reactivity indices such as local electrophilicity, the Fukui function for nucleophilic attack, and dual descriptor values of the phenolic hydroxyl oxygen along the IRC. © 2015, Springer-Verlag Berlin Heidelberg.